Chemical Composition and Cytotoxic Activity of Eruca sativa L. Seeds Cultivated in Egypt - M. Nazif, Naglaa; A.E. Habib, Amira; A.M. Tawfik, Wafaa; A. Hassan, Rasmia (Asian Journal of Chemistry, 2010)
Eruca sativa L. (family: Brassicaceae) is native to southern Europe and central Asia where it has been cultivated since classical times. It is sometimes referred to as a rocket, true rocket, rocket salad, arugula, roquette or white pepper. It is used for flavouring salads. Investigation of the 70 % alcoholic extract of E. sativa L. seeds led to the isolation of three flavonoids, quercetin (I), rhamnetin (II) and kaempferol-3-O-galactoside (III), in addition to 2-glucosinolates, 4- methylthio butyl glucosinolate (glucoerucin) (IV) and 3-methylsulfinylpropyl glucosinolate (glucoiberin) (V). The compounds were identified by the use of (TLC, PC, MS and GC/MS). The petroleum ether extract of E. sativa seeds was investigated. The fatty acid fraction was found to contain 9 fatty acids in which erucic acid represented the main component (44 %) of the total fatty acid mixture. The unsaturated fatty acids represent 90 % of the total mixture. The unsaponifiable matter constituted of mixture of n-alkanes from C16-C26, b-sitosterol, cholesterol, stigmasterol, campsterol. b-sitosterol are the major constituents, representing 28 % of the total mixture. Cytotoxic activity of total alcoholic extract of the defatted seeds and the isolated compounds were performed against several types of tumor cell lines using the SRB assay. The total alcoholic extract and the aglucones of the isolated compounds glucoerucin and glucoiberin exhibited significant cytotoxic activity for HCT116 (colon carcinoma cell line) (IC50 = 0.74, 2.42 and 0.94 μg/mL), respectively, while the IC50 was > 10 μg/mL for both Hela (Cervix carcinoma cell line), HEPG2 (liver carcinoma cell line), MCF7 (breast carcinoma cell line) and U251 (brain carcinoma cell line).